Influence of Digital Marketing, FOMO, and Influencer Marketing on Skintific Purchase Decisions in Samarinda - Farinda Hidayah Wati; Saida Zainurossalamia ZA (Golden Ratio of Data in Summary, 2026)
This study aims to analyze the influence of Digital Marketing, Fomo (Fear of Missing Out), and Influencer Marketing on purchasing decisions for Skintific skincare products in Samarinda City. The study population was Skintific product users in Samarinda City. The study used a purposive sampling technique with a sample of 128 respondents. Data were collected through a Likert scale questionnaire and analyzed using SEM-PLS with SmartPLS 3.0. The results showed that Digital Marketing, Fomo (Fear of Missing Out), and Influencer Marketing had a positive and significant effect on purchasing decisions. Digital Marketing was the most dominant variable with a path coefficient of 0.407, followed by Influencer Marketing (0.327) and Fomo (Fear of Missing Out) (0.206). The R-Square value of 0.608 indicated that 60.8% of the variation in purchasing decisions could be explained by these three variables.